DESCRIPTION OF NATURAL, ECONOMIC AND PRODUCTION FACTORS THAT INFLUENCE THE DEVELOPMENT OF WIND ENERGY IN RUSSIA - A. Borozdin (Вестник университета)
In Russia, there are all conditions for the development and construction of wind turbines systems to generate carbon free electricity. Cheap factors are the projected rise in demand for energy, the climatic conditions and the use of existing wind power on the large Russian territory. In the manufacture of pipes, the Russian oil industry and mechanical engineering industry have a modern state of the art and technology. The development of wind turbines systems can promote the oil industry in the power supply of new oil fields and the engineering industry in the development of wind energy systems.